(untitled) (Research, Society and Development, 2021)
The present paper, through research and studies of some works, makes an analysis about some learning difficulties and, in this way, present some aspects pertinent to the concepts of researchers on the theme, some classifications and the intervention in the school context. The methodology used was a bibliographic search, where we searched from several sources: articles and monographs that talked about the theme, so that we carried out a vast exploratory reading about dyslexia. When carrying out this study, our objective was to discuss some learning difficulties, elucidating several aspects pertinent to the theme, including presenting some alternatives that the teacher must take to face in the classroom. In this way, this work has its relevance, since, in our schools, many students, who are intelligent, have difficulties learning to read and perform some mathematical processes, facts that need to be minimized in order to improve teaching.